2022
DOI: 10.1016/j.celrep.2021.110211
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated post-transcriptional control of oncogene-induced senescence by UNR/CSDE1

Abstract: Highlights d CSDE1 is a tumor suppressor in primary mouse keratinocytes d CSDE1 promotes oncogene-induced senescence (OIS) d CSDE1 coordinates the two branches of OIS: proliferation and the SASP d CSDE1 enhances SASP factor mRNA stability and represses Ybx1 mRNA translation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 80 publications
1
11
0
Order By: Relevance
“…CSDE1 binding specificity is somewhat relaxed. Initial in vitro SELEX experiments indicated a purine-rich motif with a core of AAGUA/G or AACG, which has been confirmed in Bind-N-Seq experiments and in vivo iCLIP studies ( 47 , 49 , 63 , 64 ) (Figure 3A ). While these motifs might be present frequently in the transcriptome, a meta-analysis reveals a predilection for CSDE1 binding near the start codon and following the termination codon of the open reading frame, suggesting that additional features contribute to RNA-binding specificity (Figure 3B ).…”
Section: Csde1 As a Molecular Adaptormentioning
confidence: 64%
See 3 more Smart Citations
“…CSDE1 binding specificity is somewhat relaxed. Initial in vitro SELEX experiments indicated a purine-rich motif with a core of AAGUA/G or AACG, which has been confirmed in Bind-N-Seq experiments and in vivo iCLIP studies ( 47 , 49 , 63 , 64 ) (Figure 3A ). While these motifs might be present frequently in the transcriptome, a meta-analysis reveals a predilection for CSDE1 binding near the start codon and following the termination codon of the open reading frame, suggesting that additional features contribute to RNA-binding specificity (Figure 3B ).…”
Section: Csde1 As a Molecular Adaptormentioning
confidence: 64%
“…found CSDE1 loss-of-function mutations as drivers of neuroendocrine tumors with a Wnt-altered phenotype, indicating that CSDE1 is a suppressor of this tumor type ( 48 ). CSDE1 also behaves as a tumor suppressor in squamous cell carcinoma, where it promotes oncogene-induced senescence by repressing the synthesis of YBX1 and enhancing the stability of mRNAs encoding senescence-associated secretory phenotype (SASP) factors ( 49 ). In addition, tumor suppressor roles of CSDE1 can be inferred from studies in glioma, where CSDE1 was identified as the target of the drug clofoctol ( 50 ).…”
Section: Cancer Hallmarks Regulated By Csde1 and Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…45,46 Csde1 is also known to act as both a promoter and suppressor of oncogenesis in a contextdependent manner and has been shown to directly interact with TGF-β1 RNA and other related RNAs in cancer cells to influence metastasis and migration. 29,47,48 Previous data showed that Csde1 preferentially binds to the 5ʹ UTR of selective RNA targets, allowing it to impact early translational elongation. 47 We confirmed increased 5´UTR binding for endothelial Csde1 specifically on TGF-β stimulation, although we did not further investigate this mode of action in our study.…”
Section: Discussionmentioning
confidence: 99%